2008
DOI: 10.1021/bm701259r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects of Terminal Groups on Nonenzymatic and Enzymatic Degradations of End-Capped Poly(l-lactide)

Abstract: Poly(L-lactide) (PLLA) with various alkyl ester chain end groups were synthesized by ring-opening polymerization of L-lactide in the presence of zinc alkoxide as a catalyst. The structural effect of chain end groups on the rate of enzymatic and nonenzymatic degradations for amorphous films of PLLA were investigated at 37 degrees C in a Tris-HCl buffer solution (pH 8.6) with proteinase K and at 60 degrees C in a phosphate buffer solution (pH 7.4), respectively. The rate of enzymatic degradation for PLLA films w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…A plausible explanation for the slower degradation rate of all mPEGylated systems was due to the coverage of the enzymatically inactive mPEG segment on the surface of enzymatically active PHA copolymer core. A similar effect on the surface barrier was found in the degradation of hydrocarbon (C12-C14) end-capped poly(l-lactide) film by proteinase K (Kurokawa et al, 2008). They suggested that the slower degradation, compared to non-end-capped polymer film, must be due to the coverage of the hydrocarbon end groups on the surface.…”
Section: Preparation and Characterization Of Nanoparticlessupporting
confidence: 52%
“…A plausible explanation for the slower degradation rate of all mPEGylated systems was due to the coverage of the enzymatically inactive mPEG segment on the surface of enzymatically active PHA copolymer core. A similar effect on the surface barrier was found in the degradation of hydrocarbon (C12-C14) end-capped poly(l-lactide) film by proteinase K (Kurokawa et al, 2008). They suggested that the slower degradation, compared to non-end-capped polymer film, must be due to the coverage of the hydrocarbon end groups on the surface.…”
Section: Preparation and Characterization Of Nanoparticlessupporting
confidence: 52%
“…The calculated molecular weight ( M n (calc.) ) of the obtained samples was estimated from the monomer/initiator ([CL] 0 /[ threo ‐9.10‐dihydroxyoctadecanoic acid] 0 ) ratio and the polymer yield 62. These values differ from that obtained by GPC and from calculated by 1 H‐NMR spectra (Table II).…”
Section: Resultsmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9] Among aliphatic biodegradable polyesters, poly(butylene succinate) (PBS) is considered to be a promising material in many fields because it has excellent biodegradability, melt processibility and chemical resistance. However, PBS has limited applications because of its poor thermal stability and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%